IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI - Viatul Qiromah; Fitriatul Munawaroh (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
In the process of Islamic Religious Education (PAI) learning, an educator needs to prepare a learning model that is appropriate to the students’ needs. The implementation of the Inquiry learning model can be used as a solution to help overcome students’ difficulties in receiving and understanding the lesson material. The Inquiry model encourages students to be actively involved in the learning process. The purpose of this study is to describe and analyze the implementation of the Inquiry learning model in PAI lessons for seventh-grade students at MTs Negeri 3 Jember. This research is a descriptive qualitative study. Based on the observations conducted, there were different levels of learning interest among students in studying Islamic Religious Education. Efforts to increase students’ learning interest included: teachers giving questions or exercises to students which were then answered by them, and teachers providing educational games so that students became more enthusiastic about learning. Data collection was carried out through observation, interviews, and documentation. Meanwhile, the methods used for data analysis were data condensation, data presentation, and conclusion drawing. The results of this study indicate that the implementation of the Inquiry model in PAI learning at MTs Negeri 3 Jember promotes active student involvement. With such active participation, students tend to have higher motivation and enthusiasm in participating in learning activities. In addition, the learning atmosphere becomes more interactive, which helps students understand the material better. The better the implementation of the Inquiry model in the learning process, the higher the students’ interest and participation in teaching and learning activities. ABSTRAK Dalam proses pembelajaran PAI seorang pendidik perlu mempersiapkan model pembelajaran yang sesuai dengan kebutuhan siswa. Penerapan model Inkuiri dapat dijadikan solusi untuk membantu mengatasi kesulitan siswa dalam menerima dan memahami materi pelajaran. Model Inkuiri mendorong siswa terlibat secara aktif dalam pembelajaran. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis implementasi model pembelajaran inkuiri pada pelajaran PAI siswa kelas VII di MTs.Negeri 3 Jember. Penelitian ini jenis penelitian kualitatif deskriptif. Berdasarkan   hasil observasi yang dilakukan, terdapat Minat   belajar   yang   berbeda   beda   dalam mempelajari  Pendidikan  Agama  Islam. Upaya  meningkatkan  minat  belajar  siswa  diantaranya: Guru  memberikan  pertanyaan  atau  soal  kepada  murid  yang  kemudian dijawab  oleh  siswa nya, Murid  diberikan  permainan edukasi  oleh  guru  agar  mereka semangat  untuk  belajar. Pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi. Sedangkan metode untuk analisis data menggunakan kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa implementasi model Inkuiri pada pembelajaran PAI di MTs. Negeri 3 Jember Dengan adanya keterlibatan aktif tersebut, siswa cenderung memiliki motivasi dan antusiasme yang lebih tinggi dalam mengikuti pembelajaran. Selain itu, suasana belajar menjadi lebih interaktif sehingga dapat membantu siswa memahami materi dengan lebih baik. Semakin baik penerapan model Inkuiri dalam proses pembelajaran, maka semakin tinggi pula minat dan partisipasi siswa dalam kegiatan belajar mengajar.